Investment Guarantees and Incentive Law = قانون ضمانات وحوافز الاستثمار - Egypt; The middle east library for economic services, translator. (2025)
Part - I: General Provisions. 4. Part - II: Investment Guarantees. Part - III : Investment Incentives. Chapter 1: Fiscal Exemptions. .... Chapter 2: Land Appropriation. 13 Chapter 3: Free Zones.. 13 Part - IV : Facilitating Investment Procedures